To prove this inequality we need to consider three cases. We need to see that the equation is symmetric and that switching the variables x and y does not change the equation.
Thus, we can say that x^y >= 1, and since y^x > 0.
x^y + y^x > 1
By symmetry, 0 < x < 1, y >= 1, also yields the same.
Case 3: 0 < x, y < 1
We can prove this case by fixing one variable at a time and by invoking symmetry to prove the relation.
Fixing the variable y, we can set the expression as a function,
f(x) = x^y + y^x f'(x) = y*x^(y-1) + y^x*ln y For all x > 0 and y > 0, it is obvious that f'(x) > 0.
Hence, the function f(x) is increasing and hence the function f(x) would be at its minimum when x -> 0+ (this means close to zero but always greater than zero).
lim x->0+ f(x) = 0^y + y^0 = 0 + 1 = 1
Thus, this tells us that
f(x) > 1.
Fixing variable y, by symmetry also yields the same result: f(x) > 1.
Hence, when x and y are varying, f(x) > 1 must also hold true. Thus, x^y + y^x > 1.
We have exhausted all the possible cases and shown that the relation holds true for all cases. Therefore,
Use your rules of logs. First the sum of two logs with same base is the product of the parts. Log7 (5x) = log7 60. Now since both sides have same log and base the parts are equal. 5x = 60. Divide by 5 to get a result of x = 12
= a^21b^24c^10 use the product rules for each set of () then multiply them together. when multiplying variables with exponents you just add them together like for a^3 * a^5 = a^8. (a^3 b^12 c^2)^2 = (a^6 b^24 c^4)